Sustained detection of type 2 poliovirus in London sewage between February and July, 2022, by enhanced environmental surveillance. Issue 10362 (29th October 2022) - Klapsa, Dimitra; Wilton, Thomas; Zealand, Andrew; Bujaki, Erika; Saxentoff, Eugene; Troman, Catherine; Shaw, Alexander G; Tedcastle, Alison; Majumdar, Manasi; Mate, Ryan; Akello, Joyce O; Huseynov, Shahin; et al.
Summary: Background: The international spread of poliovirus exposes all countries to the risk of outbreaks and is designated a Public Health Emergency of International Concern by WHO. This risk can be exacerbated in countries using inactivated polio vaccine, which offers excellent protection against paralysis but is less effective than oral vaccine against poliovirus shedding, potentially allowing circulation without detection of paralytic cases for long periods of time. Our study investigated the molecular properties of type 2 poliovirus isolates found in sewage with an aim to detect virus transmission in the community. Methods: We performed environmental surveillance in London, UK, testing sewage samples using WHO recommended methods that include concentration, virus isolation in cell culture, and molecular characterisation. We additionally implemented direct molecular detection and determined whole-genome sequences of every isolate using novel nanopore protocols. Findings: 118 genetically linked poliovirus isolates related to the serotype 2 Sabin vaccine strain were detected in 21 of 52 sequential sewage samples collected in London between Feb 8 and July 4, 2022. Expansion of environmental surveillance sites in London helped localise transmission to several boroughs in north and east London. All isolates have lost two key attenuating mutations, are recombinants with a species C enterovirus, and an increasing proportion (20 of 118) meet the criterion for a vaccine-derived poliovirus, having six to ten nucleotide changes in the gene coding for VP1 capsid protein. Interpretation: Environmental surveillance allowed early detection of poliovirus importation and circulation in London, permitting a rapid public health response, including enhanced surveillance and an inactivated polio vaccine campaign among children aged 1–9 years. Whole-genome sequences generated through nanopore sequencing established linkage of isolates and confirmed transmission of a unique recombinant poliovirus lineage that has now been detected in Israel and the USA. Funding: Medicines and Healthcare products Regulatory Agency, UK Health Security Agency, Bill & Melinda Gates Foundation, and National Institute for Health Research Medical Research Council.